Too Cold to Venture There? January Temperature and Immigrant Self-Employment across the United States - Jun Yeong Lee; John V. Winters (Institute of Labor Economics (IZA), 2021)
Immigrant entrepreneurs are critical to regional and national economies. Immigrants in the USA have higher self-employment rates than natives, and immigrants have made outsized contributions as founders of numerous highly successful firms. However, we document that immigrant self-employment rates vary considerably across areas of the USA. Our main measure is the percentage of immigrant workers in an area who are self-employed; i.e., the self- employment rate for the foreign-born. Areas with colder winter temperatures have especially low self-employment rates among their immigrant populations compared to other areas of the USA. This relationship holds for numerous sub-samples of immigrants and is not driven by any particular group. The relationship persists after controlling for numerous individual and local area characteristics. Immigrant entrepreneurs appear to be especially forward-looking and responsive to warmer January temperature as a locational amenity. The results have important implications about the location choices of immigrant entrepreneurs.
Keywords: J61; L26; R23; 330; self-employment; entrepreneurship; immigrants; amenities; temperature